Oxidation-Triggered Formation of Diradical Cations from Paramagnetic Molecules and Their Spin Density Evolution - Di Wang; Dan Yao; Xinyu Li; Lingli Shi; Chunyuan Wang; Jie Li; Weili Kong; Yongliang Qin; Martin Baumgarten (Molecules)
Controllable intramolecular spin-polarized flow refers to the manipulation of spin-polarized electron transport within molecules through externally applied stimuli, thereby modulating their intramolecular spin characteristics and magnetic properties. In this work, we designed and synthesized four paramagnetic molecules, PDTN-NN, PDTN-IN, PO-NN, and PO-IN, by introducing nitronyl nitroxide (NN) and iminonitroxide (IN) radicals into phenothiazine and phenoxazine frameworks. Remarkably, we successfully generated the corresponding radical-substituted radical cations (diradical cations) and controlled their spin density distributions (SDDs) through redox stimuli. UV-Vis absorption spectroscopy, cyclic voltammetry (CV), electron paramagnetic resonance (EPR), and density functional theory (DFT) were employed to confirm the formation of diradical cations during the redox processes. Furthermore, EPR spectroscopy and DFT calculations were also employed to provide clear evidence of intramolecular magnetic coupling in the diradical cations.